Knowledge and Understanding about Government Procurement and Supplies Management Act B.E. 2560 and Efficiency of Supplies Management of Procurement Officers in Community Hospitals - Chuenwiset, Thitima; Aujirapongpan, Somnuk; Ritkaew, Supit (Business Administration and Economics Review, 2022)
The objectives of this study were to: 1) Study the level of knowledge and understanding about Government Procurement and Supplies Management Act B.E. 2560, of Procurement Officers in Community Hospitals, 2) Study the efficiency of parcel management, of Procurement Officers in Community Hospitals and 3) Study the factors related to the efficiency of parcel management of Procurement Officers in Community Hospitals. By setting the scope of education in Community Hospitals, Health Region 11. The sample of this study was 90 samples, The workers involved in the procurement work are the positions of procurement officers and procurement scholars, of Procurement Officers in Community Hospitals, Health Region 11. Gathering data from the test. The data analysis used statistical software with the significance level of 0.05. The statistics, were used to frequency, percentage, means, standard deviation, t-test, F-test, and Pearson correlation. The results found that the study on the level of knowledge and understanding of Procurement Officers in Community Hospitals, Health Region 11, were found to be moderate in the part of the study on the efficiency of parcel management of the parcel staff in Community Hospitals, Health Region 11, with a level of efficiency Demand planning at a high-level Distribution efficiency at the highest level and maintenance efficiency is moderate It was found that the efficiency related to personal factors was the position, responsibility. Have been appointed as a committee to perform duties by the rules of the governor’s office by procurement 1992 and its amendments and the number of personnel in the management of supplies especially those who work in supplies are sufficient. At a statistically significant level of 0.05 by factors related to the efficiency of the parcel management of the parcel staff Community Hospitals, Health Region 11 by Positive Relationships Statistical significance level 0.05.